Association Of C-Reactive Protein And Modified Rodnan Skin Score With Carotid Intima-Media Thickness in Systemic Sclerosis - Permadi, Dody Tri; Hellmi, Rakhma Yanti; Limantoro, Charles (RSUP Dr. Kariadi, 2026)
BACKGROUND: Systemic sclerosis (SSc) is a chronic autoimmune disease characterized by vasculopathy and progressive fibrosis with an increased risk of cardiovascular disease. The common carotid artery intima-media thickness is an indicator of subclinical atherosclerosis and may reflect inflammatory activity in SSc. Quantitative C-reactive protein (CRP) and the modified Rodnan Skin Score (mRSS) are associated with SSc disease activity, although their relationship with common carotid intima-media thickness remains unclear. AIMS: To evaluate the relationship between quantitative CRP levels and mRSS values with common carotid intima-media thickness in adult patients with SSc. METHOD: A cross-sectional study was conducted on 26 SSc patients at Dr. Kariadi General Hospital, Semarang. Common carotid intima-media thickness was measured using ultrasonography on both sides. Subjects were categorized based on the presence of intima-media thickening according to the ≥75th percentile for age and sex. Quantitative CRP levels were analyzed using the Mann-Whitney test, while differences in mRSS were analyzed using an independent T-test. RESULT: Increased common CIMT was observed in 9 patients (34.6%). There was no significant difference in quantitative CRP levels between subjects without and with intima-media thickening (0.40 [0.07–1.10] vs. 0.40 [0.20–0.83] mg/L; P = 0.787). mRSS values also did not differ significantly between the two groups (18.29 ± 9.38 vs. 18.78 ± 12.48; P = 0.912). CONCLUSION: There was no significant relationship between quantitative CRP levels or mRSS values and common carotid intima-media thickness in patients with SSc. These findings may be influenced by immunosuppressive therapy and study design.